Experimental proof on the effect of beam width and spatial coherence on Goos-Hänchen shift. (April 2023) - Zhu, Guiyuan; Gao, Binjie; Zhang, Junxiang; Wang, Li-Gang
Highlights: The effects of beam width and spatial coherence on Goos-Hänchen (GH) shift of light are experimentally investigated. GH shifts are influenced by beam width and spatial coherence. This result is qualitatively consistent with the prediction of coherence theory. The giant GH shift is measured near the angles of resonant peaks in the double-prism structure. Abstract: We have experimentally investigated the effect of beam width and spatial coherence on Goos-Hänchen (GH) shift of light in a double-prism structure. The beam width and spatial coherence of the incident light are well controlled and measured. The experimental results show that the GH shift is affected by both the beam width and spatial coherence of light, and this is qualitatively consistent with the prediction of coherence theory of light. The result can promote the application of controlling GH shifts of partially coherent finite beams in optical devices and sensors.